Różnicowanie pracowników ze względu na dziedzictwo genetyczne w prawie polskim - Zoń, Katarzyna Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
This study focuses on the problem of the possibility of discrimination against employees or future employees based on their genetic heritage. This issue is related to the dynamic development of modern genetics the effects of which are perceptible in labor relations.At the beginning of above considerations is the relationship between the scope of personal data which employer may demand to provide Article 221 of the Labor Code and employee’s genetic data. In this context admissibility of carrying out genetic tests in employment should be taken into consideration. The most significant in this respect is the principle of equal treatment of employees Article 183a of the Labor Code. According to the above-mentioned provision, employees should be treated equally in relation to each aspect of the employment relationship. Catalogue of prohibited discrimination criteria contains a phrase “in particular.” Therefore, it may include other prohibited grounds for discrimination, such as genetic heritage. This thesis finds support in rules of international law which set standards in this area. To sum up, genetic heritage is not an acceptable criterion of differentiation between employees. Current regulations of Polish labor law may be insufficient when confronted with new medical technologies and may need an improvement in this respect.
Keywords: dziedzictwo genetyczne; równe traktowanie w zatrudnieniu; zakaz dyskryminacji w zatrudnieniu; dane genetyczne; testy genetyczne w zatrudnieniu